Tools for the hospital team
1947-07-14 1947 1940s 1 page 14/7/47 - No.3 TOOLS FOR THE HOSPITAL TEAM Good tools are essential to reduce unnecessary work in hospitals, said the Minister of Health, Mr. Aneurin Bevan, opening the Hospital Domestic Aids Exhibition today (Monday July 14th). To give hospital authorities the chance to see new labour saving devices this Exhibition, held at the premises of the Empire Tea Bureau, Regent Street, S.W.1. has been arranged on behalf of the Ministry of Health by the British Electrical Development Association with the British Gas Council. Emphasising the importance of good domestic organisation in hospitals, Mr. Bevan mode these points:- Hospitals must attract domestic staff of good calibre to secure the best results. Their status as vital members of the team should be firmly established and their contribution as members of the team fully recognised. Systematic training and a proper ladder of promotion to higher domestic posts are desirable. Good welfare arrangements and good tools are necessary and the employment of men to handle the heavier equipment advisable. The "good tools" displayed at the Exhibition are being produced now, but some waiting may be unavoidable before orders can be fulfilled, particularly in equipment containing sheet steel. "There are signs that the supply of domestic workers is beginning to improve", said Mr. Bevan. "Over 2,500 women from displaced persons camps in Germany were brought in during the winter and are proving a great help in many hospitals, including sanatoria, where nurses much burdened with domestic duties have been freed to concentrate on nursing". Mr. Bevan instanced one sanatorium in the North where the nursing staff until recently swept and dusted and cleaned bathrooms and lavatories while the night nurses washed the dining room floors and cleaned the fireplaces. Since the arrival of some Estonian workers they have been able to devote themselves exclusively to the patients and their treatment. Because of the need to frrr [free] the nurses from domestic work hospitals are being urged to review their arrangements and put their extra demands for domestic workers to the Ministry of Labour. MINISTRY OF HEALTH 292/842/2/36